Stock Market Analysis of 10 Different Countries in the Period of Disease COVID-19 - Dr. Leena Sharma; Aditya V. Yadav; Shravani P. Ahirrao; Varun S. Manik; Aman S. Ramani (International Journal of Engineering and Management Research, 2020)
Our effort is to analyze the effect of the rampant over the economies of 10 affected nations by studying their stock market values during the COVID-19 episode. We have endowed the nations with their respective stock markets stated in brackets - Brazil(Ibovespa), Canada (S&P/TSX Composite), France (AEX), Germany (DAX 30), India (NIFTY 50), Italy (FTSE MIB), Russia (IMOEX), Spain (IBEX 35), U.K. (FTSE 100), U.S.A. (DOW JONES INDUSTRIAL AVERAGE). We have gathered the indices of stock per country from 2 March to 23rd June, collected from official website of respective stocks. In order to collect data, we had to inculcate the fundamental lessons of Statistics. R-software aided us to plot the curves of stock values providing an ease to master our project. We also formulated a Python 3.7 language program code to solidify analysis on various aspects of economy of the countries and comparison between these aspects.